PENGARUH PENGGUNAAN MEDIA FLASHCARD PADA MATA PELAJARAN BAHASA INGGRIS DALAM MENINGKATKAN MINAT DAN KEAKTIFAN SISWA KELAS V SD NEGERI PODOSUGIH 01 KOTA PEKALONGAN - Hidayati, Annisa Tri; Andaryani, Eka Titi (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2025)
This research is motivated by the lack of interest in learning students and the lack of student activity in learning English. The method used is quantitative research with a research design, namely one group pretest posttest. The sample research is class 5. The results of the study showed that the results of the pretest of student interest were seen from the average value of 40.5. The results of the pretest of student activity were seen from the average value of 9.77. The results of the posttest of student interest were seen from the average value of 52.6 and the results of the posttest of student activity were seen from the average value of 42.2. The results of the t test on student interest were the value of thitung = 13.922> ttabel = 2.042 meaning that h0 was rejected while ha was accepted. And for the results of the t-test on student activity is the value of thitung = 10.922 > ttabel = 2.042 meaning h0 is rejected while h0 is accepted. It is concluded that there is an influence on the use of flashcard media in increasing student interest in English subjects in grade V of Podosugih 01 Elementary School.